Challenges Facing the European Union in Taxing the Digital Economy - Wiatrowski, Roman (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The world of the digital economy is constantly evolving and will be the main vehicle for global trade in the future. The transfer of transactions to the Internet requires appropriate tax regulations that, on the one hand, prevent tax fraud and abuse, and, on the other hand, facilitate e-commerce by removing tax obstacles. International institutions are taking initiatives to regulate these issues on a global basis. The article attempts to examine to what extent global initiatives have been implemented in the European Union and what challenges the European Union faces due to the limited success of these global initiatives. This required a recasting of current EU regulations and the prospects facing the European Union in relation to the need for the effective taxation of the rapidly growing digital economy, in which digital platforms play a particular role.